The impact of organizational efforts on process satisfaction and purchase intention with emphasizing on the role of mediator of consumer concerns in an online context - Bagheri, Roghayeh; Doroudi, Homa (British Journal of Marketing Studies, 2017)
The main of this study, was “The impact of organizational efforts to process consumer satisfaction and purchase intention with emphasizing on the role of mediator consumer concerns an online context, in the e-store "Jahesh book". The present study is an applied research. It is also a survey conducted based on descriptive-analytical method. The study population included the Jahesh book, s customers. 170 of them were selected based on simple random sampling. In order to collect data, local standard questionnaires that its reliability Alpha total (0/869) and its validity using factor analysis KMO (0/796) validity was confirmed. Research hypotheses were tested using structural equation and Spss22 as well as Lisrel software was used for data analysis. The results, using path analysis shows that Order fulfilment, absence of error and trust online have a negative impact on perceived risk. Also, order fulfilment, brand image, Reduction of security and privacy concerns, have significant positive impact on online trust. Positive impact of absence of errors and reduction of security concerns on reduction of privacy concerns, was approved. Brand image also has a significant positive impact on reduction of security concerns. Reduction of security and privacy concerns, online trust and satisfaction have a significant positive impact on purchase intention. Perceived risk has a significant negative impact on satisfaction and purchase intention. The positive effect of visual effects, online trust, reduction of security and privacy concerns on satisfaction were approved. Of course, the impact of visual appearance on online trust and reduction of security concerns were not confirmed.